Temporal Ontologies in Intelligent Situation Awareness Systems - VEREMEIENKO, ANDRII; KUNANETS, NATALIA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Temporal Ontologies in Intelligent Situation Awareness SystemsThis article addresses the problem of formal knowledge representation in modern situation awareness (SA) systems. Special attention is given to the use of temporal ontologies, particularly OWL-Time, SOSA, and CNTRO, as effective tools for modeling the temporal characteristics of events, including their sequence, duration, and interrelations. The paper provides a comprehensive analysis of contemporary approaches to temporal modeling in ontologies, such as Allen’s interval algebra, temporal extensions of RDF, and the SPARQL query language with temporal constraints. Architecture for SA systems is proposed, which incorporates data acquisition, semantic annotation, ontological representation, temporal reasoning, and presentation layers, with a strong focus on implementation using .NET technologies and libraries for RDF/OWL processing. Furthermore, the paper examines practical examples of how temporal ontologies are applied in various domains, including cybersecurity, emergency management, environmental monitoring, and the Internet of Things. A comparative review of recent academic publications confirms the relevance and effectiveness of temporal modeling in enhancing the accuracy and reliability of situation assessment. The potential for adapting existing ontologies to address challenges involving incomplete or fuzzy temporal information is also substantiated. The results of this study can be applied to the development of intelligent security, monitoring, and cognitive systems operating in real-time environments. Future research directions include the integration of temporal ontologies with neural network models for automated discovery of temporal patterns, and the advancement of formal tools for handling uncertain or imprecise time intervals. The proposed approach lays the groundwork for the development of flexible, adaptive, and semantically rich situation awareness systems.Keywords: situation awareness, intelligent systems, temporal ontologies, OWL-Time, Allen’s interval logic.
Keywords: situation awareness; intelligent systems; temporal ontologies; OWL-Time; Allen’s interval logic